Stage IV colorectal cancer presenting after necrotizing soft tissue infection. Issue 1 (2nd January 2021) - Freedle, Caroline; Rahesh, Jasmin; Harris, Michelle; Tran, Virginia; Dissanaike, Sharmila
Abstract: Necrotizing soft tissue infections (NSTIs) are highly aggressive and may be lethal if untreated. Polymicrobial infections of the groin and lower limb have been documented secondary to invasive colorectal cancer (CRC). We present a case of CRC diagnosed more than 4 years after the development of NSTI. There are documented cases of NSTIs concomitant with a preexisting CRC. In this case, however, the patient's initial presentation was an NSTI followed by later diagnosis of CRC. A previously treated NSTI that is not healing appropriately may be an early indicator for CRC.